Technical report: d' Alembert formula for wave equation / Farhana Jamil and Radin Ummu Hidayah Radin A. Kadir - Jamil, Farhana; Radin A. Kadir, Radin Ummu Hidayah (2016)
The title of this project is d' Alembert Formula for Wave Equation. The purpose of this project is to solve the wave equation problem by using d' Alembert formula and show that the wave is traveling towards opposite directions. First, d' Alembert formula is derived from the wave equation. Then, a few wave problems have been chosen and solved. Various graphs have been plotted by using Maple Software, which show that it is proven the wave is traveling towards two opposite directions. After all of the three steps of methodology have been done, the results achieved is as wanted. The results have shown that the d' Alembert formula can be used to solve wave equation problems. 1bis formula also can be used to prove that the wave is travelling in two opposite directions.